2014
DOI: 10.1080/07294360.2014.911261
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing large-class teaching: a systematic comparison of rich-media materials

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Other studies have endorsed this and found that, generally speaking, the availability of recorded lectures has little to no effect on student attendance at live lectures (Holbrook & Dupont, 2009;Pursel & Fang, 2012;Saunders & Hutt, 2015;Von Konsky, Ivins, & Gribble, 2009). In Saunders and Hutt's (2015) study, for instance, students used recorded and face to face lectures for different purposes. The former were mainly utilised to address the gaps in students' knowledge, revise learning material and prepare for exams (which is consistent with the findings reported here), while they appreciated the latter for an opportunity to gain more comprehensive information and to ask questions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have endorsed this and found that, generally speaking, the availability of recorded lectures has little to no effect on student attendance at live lectures (Holbrook & Dupont, 2009;Pursel & Fang, 2012;Saunders & Hutt, 2015;Von Konsky, Ivins, & Gribble, 2009). In Saunders and Hutt's (2015) study, for instance, students used recorded and face to face lectures for different purposes. The former were mainly utilised to address the gaps in students' knowledge, revise learning material and prepare for exams (which is consistent with the findings reported here), while they appreciated the latter for an opportunity to gain more comprehensive information and to ask questions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that students do not tend to replace attendance at face to face lectures with ilectures (Gorissen, Van Bruggen, & Jochems, 2012;Gupta & Saks, 2013;Karnad, 2013;Larkin, 2010;Mather, Caesar, Chin, & Fei, 2015) but instead prefer a blended learning approach where they mix a little of both modes together (e.g., Zeldenryk & Bradey, 2013). A study conducted by Saunders and Hutt (2015) in a British university revealed that only 10% of the participants (n=84) resorted to ilectures as a substitute for face-to-face instruction. Other studies have endorsed this and found that, generally speaking, the availability of recorded lectures has little to no effect on student attendance at live lectures (Holbrook & Dupont, 2009;Pursel & Fang, 2012;Saunders & Hutt, 2015;Von Konsky, Ivins, & Gribble, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rich-media material considered in these studies is also in a variety of formats including audio-only podcasts, enhanced podcasts, video segments, or full lecture capture. It is also important when examining the use of rich-media resources to consider also the pedagogy as well as the preference of the students and the purpose of the resource; this is mentioned in Van Zanten et al (2012) with their 3Ps and has been recently extended by Saunders and Hutt (2015) to include a fourth P of the performance of the students.…”
Section: Introductionmentioning
confidence: 99%
“…Students at Satellite ask fewer questions than students at Main; nor do they have the opportunity for an informal discussion once a formal session has ended: indeed, even if a Satellite student were inclined to listen in to such a discussion, the automatic shutoff function of the conferencing software would prevent this from being possible. Students at both sites make good use of digital resources, but the Satellite students also wish that opportunities for face-to-face teaching were more prevalent (Saunders and Hutt, 2014). Not all students -regardless of their physical locationwant to see themselves on screen when they ask questions.…”
Section: Conclusion: Contrasting Rhetoric and Realitymentioning
confidence: 99%